1955
DOI: 10.1063/1.1722053
|View full text |Cite
|
Sign up to set email alerts
|

Resonant-Cavity Field Measurements

Abstract: The application of perturbation techniques to the quantitative measurement of both relative electric and relative magnetic fields in resonant cavities is described. The apparatus, procedures, advantages, and limitations are discussed, and the experimental results are compared with the calculable field distributions of a coaxial resonator. The theoretical shunt impedance and Q obtained empirically agree, respectively, within one and four percent of the calculated values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1956
1956
2002
2002

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The application of the Slater perturbation theorem to a spherical bead of relative permittivity r and permeability µ r showed that the fractional frequency deviation [17] is…”
Section: Electric Field Profilesmentioning
confidence: 99%
“…The application of the Slater perturbation theorem to a spherical bead of relative permittivity r and permeability µ r showed that the fractional frequency deviation [17] is…”
Section: Electric Field Profilesmentioning
confidence: 99%
“…in resonant frequency of' several cavities and the volume, shape and properties of the perturbation sample has been investigated by several authors (e.g. Slater 1946, Maier and Slater 1952a, b, Gilardini 1954, Kitchen and Schelberg 1955, Scaglia 1965, Brodwin and Parsons 1965, Hall 1969. This phenomenon has been used to study the properties of conducting and/or dielectric materials of different shapes by means of different cavities.…”
Section: Outline Of Theorymentioning
confidence: 99%
“…Since the efficiency of interaction between the electron beam and the microwave field depends on the field distribution, a measure of the field pattern is of importance to understand the behaviour of the gyrotron. In this paper we describe the results from measurements based on the use of the frequency shift induced by a localized dielectric perturbation [3,4,5,6]. The method is applied to the two types of Fabry-Perot resonators mentioned earlier.…”
Section: Introductionmentioning
confidence: 98%